El Aprendizaje Basado en el Pensamiento como Metodología en la Enseñanza de Biodiversidad del Ecuador: Flora, Fauna y Especies en Peligro de extinción con los estudiantes del sexto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Villacres Chango, Alison Vanessa (2024)
Biodiversity of Ecuador: Flora, Fauna, and Species in Danger of Extinction is a significant subject in educational training, which requires not only the memorization of content but also its understanding to achieve a deep understanding. At the National University of Chimborazo, Faculty of Human Education Sciences and Technologies, the sixth-semester students of the Pedagogy of Experimental Sciences Chemistry and Biology degree, the use of appropriate teaching methodologies to optimally address the different topics, since there are various problems in the educational process, one of them is the diversity of learning. The objective of the research was to propose Thinking-Based Learning (TBL) as a biodiversity teaching methodology through the Google Classroom platform, where learning activities were designed for units I and II of the subject. The research design was quantitative, non-experimental, field, bibliographic, and descriptive. The study population was made up of 20 students enrolled in the biodiversity subject. To collect the data, the survey was used as a technique, and the Google Forms questionnaire was used as an instrument. It was concluded that Thinking-Based Learning is an active methodology that promotes the way of educating as it guides more efficient learning where it strengthens the students' reasoning to develop the ability to think critically. It is recommended to apply the TBL methodology during your teaching work to adapt to the needs of your students.